Determination of arsenic, copper and lead in the water of villages of Chalkidiki, Greece - Maria A Anagnostopoulou; Neil I Ward (Open Journal of Chemistry - Peertechz Publications, 2019)
Arsenic, copper and lead are all toxic above a minimum concentration and therefore USEPA (United States Environmental Protection Agency) and European Council Directive proposed the Maximum Contaminant Level (MCL) for drinking water to be as follows: arsenic 10 ppb, copper 1,3 ppm and lead 15ppb.Human health effects due to arsenic are characterised by skin lesions observed as melanosis and keratosis. Chronic arsenic exposure can lead to neurological, cardiovascular, respiratory effects, or cause skin, bladder and lung cancer [1-3]. The severe health implications from the high arsenic intake reported in West Bengal, Bangladesh, Taiwan and Inner Mongolia [4-6], were mainly caused by the high levels of inorganic arsenic in water.